2004
DOI: 10.14712/18059694.2018.92
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase – Positive Innervation of the Spleen in Rats

Abstract: Innervation of the spleen in rats was studied. Butyrylcholinesterase-(BuChE)-positive nerve components of the organ were visualized by the direct thiocholine method. BuChE-positive nerve components enter the spleen in a common bundle with arteries. In the organ they form characteristic periarterial and periarteriolar plexiform arrangements, which are especially conspicuous around the aa. centrales running through the white pulp. Then, nerve fibres extend away from these plexuses into adjacent layers of trabecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…We will study this issue in future studies under the informed consent of patients. Furthermore, Sirotakova et al [ 51 ] showed that the splenic sympathetic nerve, accompanied by the splenic artery entering the spleen, regulates spleen haemoperfusion and the immune function of the spleen lymphocytes; MacNeil BJ et al [ 52 ] found that the relationship between the electrophysiological activity of the spleen and endotoxins occurred in a dose-dependent manner. That is, with more endotoxins, we could see higher activity intensity of the spleen sympathetic nerve, a shorter incubation period and less haemoperfusion of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…We will study this issue in future studies under the informed consent of patients. Furthermore, Sirotakova et al [ 51 ] showed that the splenic sympathetic nerve, accompanied by the splenic artery entering the spleen, regulates spleen haemoperfusion and the immune function of the spleen lymphocytes; MacNeil BJ et al [ 52 ] found that the relationship between the electrophysiological activity of the spleen and endotoxins occurred in a dose-dependent manner. That is, with more endotoxins, we could see higher activity intensity of the spleen sympathetic nerve, a shorter incubation period and less haemoperfusion of the spleen.…”
Section: Discussionmentioning
confidence: 99%